2020
DOI: 10.1097/md.0000000000019544
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D status with coronary artery disease in postmenopausal women

Abstract: The relationship between coronary artery disease (CAD) and low serum 25-hydroxyvitamin D (25(OH)D) levels has emerged. Postmenopausal (PM) women are at increased risk of CAD and vitamin D (VitD) deficiency. To investigate the relationship between CAD and VitD levels in PM women. This case–control study included 93 consecutive female patients aged 50 to 79 years old undergoing coronary angiography for evaluation of CAD and 119 age-matched controls. Serum 25(OH)D concentrations were classed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The association between vitamin D deficiency and CAD has been investigated in several studies [ 25 , 26 , 27 ]. In 1978, a Danish report initially found that vitamin D levels were significantly lower in patients with stable angina or acute myocardial infarction (AMI) than in controls [ 28 ].…”
Section: Vitamin D and Coronary Artery Diseasementioning
confidence: 99%
“…The association between vitamin D deficiency and CAD has been investigated in several studies [ 25 , 26 , 27 ]. In 1978, a Danish report initially found that vitamin D levels were significantly lower in patients with stable angina or acute myocardial infarction (AMI) than in controls [ 28 ].…”
Section: Vitamin D and Coronary Artery Diseasementioning
confidence: 99%
“…It has been shown in previous studies that in patients with type 2 diabetes, there is a strong association between low levels of vitamin D and coronary artery disease, cerebrovascular disease, and peripheral vascular disease [13,14]. In high-risk diabetics with a UACR > 30 mg/24 hours, low levels of vitamin D are associated with asymptomatic CAD [15].…”
Section: Introductionmentioning
confidence: 95%